28 Sex- and age-differences in native t1 relaxation times in healthy adults at 1.5 and 3.0 tesla. (26th April 2015) - Rauhalammi, S; Barrientos, P Hall; Carrick, D; McComb, C; Mangion, K; Clerfond, G; McClure, J; Radjenovic, A; Berry, C
Abstract : Background: Limited information is available on sex differences in myocardial T1 relaxation times over age ranges. We used cardiac magnetic resonance (CMR) imaging at two field strengths to assess myocardial T1. Methods: Healthy adults underwent CMR at 1.5 Tesla (T) (Avanto) and 3.0 T (Verio). T1 maps were acquired in three short axis slices, using an optimised MOLLI investigational prototype sequence (Siemens Healthcare WIP 448). Global mean T1, in milliseconds (ms), was calculated from evaluable regions-of-interest using 16-segment model. Results: 84 volunteers (43 male) underwent scans 1.4 ± 1.4 days apart. Because of artefacts related to cardio-respiratory motion and susceptibility effects, 47 (3.9%) segments were excluded at 1.5 T and 81 (6.3%) segments at 3.0 T, with a preponderance occurring at the distal slice. Age-related decrease in T1 was observed in females, whereas male T1 remained reasonably constant (Figure 1 and Table 1 ). At 1.5 T, amongst those <40 years T1 was higher for females (961.3 ± 19.3 ms) than males (932.0 ± 22.8 ms, p < 0.001), whereas there was no difference in those ≥60 years (937.2 ± 28.7 vs. 934.3 ± 24.3 ms, respectively, p = 0.807). Results were similar at 3.0 T; female T1 was higher at <40 years (1166.0 ± 41.7 vs. 1139.6 ± 26.1 ms, p = 0.044), but not at ≥60 years (1151.0 ± 39.3 vs. 1124.3 ± 31.6 ms, p = 0.087). Regression analysis shows that at 1.5 T average T1 decreases by 5.13 ms for each additional decade (p = 0.038). An identical trend was observed at 3.0 T, with regression coefficient −0.564 ms/year approaching statistical significance (p = 0.064). Conclusions: In healthy adults, sex difference in global myocardial mean T1 relaxation times are observed amongst younger. This pattern is consistent across CMR field strengths. Pre- vs. post-menopausal differences in myocardial structure and function of females may explain these differences and this possibility merits further assessment.